2017
DOI: 10.1680/jmacr.17.00015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cement and aggregate type on steam-cured concrete – an experimental study

Abstract: The effects of aggregate and cement type on the properties of steam-cured concrete were explored. Ordinary Portland cement (OPC) and high early strength cement (HESC) were used as binders, and recycled and natural aggregates were used as inert mineral filler aggregates in the concrete. The developed concretes exhibited adequate levels of compressive strength after steam curing. Depending on the type of coarse and fine aggregates utilised, the concretes incorporating OPC developed 42–72% of their design strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Additionally, the curing process may reduce the concrete strain due to shrinkage (86,87). In a recent research, Hanif et al (88) reported that the use of recycled aggregates with high early strength cement and steam curing method led to an improvement of shrinkage performance, lowering early-age cracking.…”
Section: Shrinkagementioning
confidence: 99%
“…Additionally, the curing process may reduce the concrete strain due to shrinkage (86,87). In a recent research, Hanif et al (88) reported that the use of recycled aggregates with high early strength cement and steam curing method led to an improvement of shrinkage performance, lowering early-age cracking.…”
Section: Shrinkagementioning
confidence: 99%
“…Several researchers have reported coarse aggregates with good morphology can provide enough strength and good structural stability to the asphalt pavement [14][15][16]. Beside the crushed stone aggregate, the recycled aggregates' abrasion resistance and morphological characteristics also have a significant effect on the pavement performances of asphalt mixture [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Steam-cured concrete is cured in elevated temperature environment to obtain high strength in early age (generally less than 20 hours after casting), which can improve the efficiency of concrete production, reduce the construction time and generate significant economic benefits [6]. In some recent research, steam-cured is even combined with high early strength cement for faster strength growth [7][8][9], where the 1 day strength can typically reach 70% of the design strength [7]. Owing to above advantages, steam-cured concrete is commonly used in prefabricated elements of high-speed railway foundation structure in China, such as girder, track slab and sleeper.…”
Section: Introductionmentioning
confidence: 99%